2017
DOI: 10.1159/000480381
|View full text |Cite
|
Sign up to set email alerts
|

Screening Performance of Placental Growth Factor for the Prediction of Low Birth Weight and Adverse Intrapartum and Neonatal Outcomes in a Term Low-Risk Population

Abstract: Introduction: Fetuses who fail to reach their genetic growth potential are thought to have sub-optimal placental function. Low placental growth factor (PlGF) levels have been shown to be predictive of placentally mediated conditions, such as pre-eclampsia or fetal growth restriction. We investigated the screening performance of PlGF for the prediction of low birth weight (<10th centile for gestation) and adverse intrapartum and neonatal outcomes in apparently low-risk term pregnancies. Materials and Methods: M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
9
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 23 publications
4
9
0
1
Order By: Relevance
“…Our results are also consistent with those of a prospective study of 438 low-risk pregnancies in which serial measurements of serum PlGF were carried out from 36 weeks' gestation until delivery; the study found that low PlGF level was associated with low birth weight and adverse intrapartum and neonatal outcomes, but the predictive performance of low PlGF was poor, with detection rate of 10-11% at FPR of 10% 22 . In contrast, a prospective study in 3747 singleton pregnancies of nulliparous women reported that elevated sFlt-1/PlGF ratio (> 85 th percentile) at 36 weeks' gestation in combination with EFW < 10 th percentile predicted 38% of adverse perinatal outcomes, at a screen-positive rate of 3% 23 .…”
Section: Comparison With Findings From Previous Studiessupporting
confidence: 87%
“…Our results are also consistent with those of a prospective study of 438 low-risk pregnancies in which serial measurements of serum PlGF were carried out from 36 weeks' gestation until delivery; the study found that low PlGF level was associated with low birth weight and adverse intrapartum and neonatal outcomes, but the predictive performance of low PlGF was poor, with detection rate of 10-11% at FPR of 10% 22 . In contrast, a prospective study in 3747 singleton pregnancies of nulliparous women reported that elevated sFlt-1/PlGF ratio (> 85 th percentile) at 36 weeks' gestation in combination with EFW < 10 th percentile predicted 38% of adverse perinatal outcomes, at a screen-positive rate of 3% 23 .…”
Section: Comparison With Findings From Previous Studiessupporting
confidence: 87%
“…Levine et al found that PlGF levels were lower in women who developed preeclampsia associated with a SGA infant compared with an appropriate for gestational age (AGA) infant (7). Studies have also shown lower PlGF levels in normotensive women delivering a SGA infant compared to normotensive women with an AGA infant (41,42,58). However, SGA infants may simply be constitutionally small without any element of placental dysfunction and thus lower PlGF levels may not always be observed (10,44).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…We have previously shown that a CPR threshold of <10th centile appears to be a good discriminator for identifying fetuses at risk of intrapartum compromise. 33 Our recent publication 34 assessing the utility of a screening test for intrapartum fetal compromise at term incorporating the CPR and maternal PlGF levels showed that the sensitivities, specificities and positive likelihood ratios for caesarean section for intrapartum fetal compromise were 100%, 86% and 7.14%, respectively. Combining both measures in the predictive model substantially improved the results of either element alone, raising the possibility that this might be a reasonable way to screen for this complication at term.…”
Section: Introductionmentioning
confidence: 99%